QARAQALPAQ XALÍQ DÁSTANÍ “EDIGE” HÁM ONÍŃ POETIKASÍNDAǴÍ AYÍRÍM MÁSELELER - Nizamatdinov, Jeńis Minajatdinovich (ILIM hám JÁMIYET, 2026)
The article analyzes the ideological, thematic, and historical aspects of the plot of the Edige epic. Also, the versions of the dastan among the Turkic peoples and the variants of the zhyrau were studied in comparison.